A new invasive species of Kerria Targioni-Tozzetti (Hemiptera: Coccomorpha: Kerriidae) on rain tree, Albizia saman (Fabaceae) from India. (3rd April 2021) - Talukder, Bipradeb; Das, Bijan K.
ABSTRACT: A new lac insect pest, Kerria destructor Talukder and Das, sp. nov . (Kerriidae) infesting the rain tree ( Albizia saman ), is described and illustrated based on the adult female, and a key to the known species of Kerria is provided. Recently, this species has been reported causing severe dieback on the twigs and branches leading to the death of a large number of rain trees in West Bengal, India. No previous records of such a destructive lac insect infestation on rain tree from India are known. Its invasive characters are discussed. http://www.zoobank.org/urn:lsid:zoobank.org:pub:67D8D166-5D7B-47A5-B867-3C9A5B049E35